A Case of Polymyxin b-Immobilized Fiber Column Treatment for Rapidly Progressive Interstitial Pneumonia Associated with Clinically Amyopathic Dermatomyositis - Oh Sasaki; Makoto Dohi; Hiroaki Harada; Mitsuru Imamura; Yumi Tsuchida; Kensuke Yamaguchi; Toshihiko Komai; Kazuhiko Yamamoto (Case Reports in Medicine)
We report a case of rapidly progressive interstitial pneumonia associated with clinically amyopathic dermatomyositis who responded to single course of polymyxin b-immobilized fiber column treatment. Initial treatment with pulsed corticosteroids and cyclophosphamide, intravenous immunoglobulin, and cyclosporine seemed to suppress the activity of interstitial lung disease temporarily, but signs of relapse were detected such as elevation of serum KL-6 level and progressing pulmonary shadows in chest computed tomography scan. After polymyxin b-immobilized fiber column treatment, the areas of pulmonary shadows drastically decreased. Gradually, arterial partial pressure of oxygen/fraction of inspired oxygen (PaO2/FiO2) ratio recovered, and serum ferritin level and KL-6 level decreased. These findings indicate that polymyxin b-immobilized fiber column treatment could be promising in combination with conventional therapy for rapidly progressive interstitial pneumonia associated with clinically amyopathic dermatomyositis, especially at the early phase of relapse.